Nutritional behaviors and dietary recommendations for figure skaters - Duffine, A. E.; Volpe, S. L. (The science of figure skating, 2018)
The aims of this chapter are to provide an overview of the macro- and micronutrient intake, as well as the eating attitudes and behaviors of figure skaters. A description of methods to evaluate energy intake and expenditure along with the resulting balance/availability is presented. Finally, hydration and blood biomarkers are discussed.